2012
DOI: 10.2174/1874149501206010239
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Solar Panel Waste Glass as a Partial Replacement of Meta-kaolinite in the Production of Geopolymers

Abstract: This investigation elucidates the mechanical characteristics of geopolymer containing solar panel waste glass. With the SiO2/Na2O molar ratio (S/N = 0.75, 1.0, 1.25, 1.5, 1.75), the percentage of metakaolinite that is replaced by so-lar panel waste glass (0- 40%), and the curing time of 1, 7, and 28 days as the study variables, the porosity, density, setting time, compressive strength, and flexural strength of the geopolymer were evaluated. The morphology of geopolymer was examined using Scanning Electron Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other types of waste glass, such as solar panel residue glass, have also been utilised in laboratory studies as a partial replacement material in metakaolin‐based activated cements. Although material performance seemed acceptable on a lab scale, the applicability of such processes (or those including post‐consumer glasses from electronic items such as display screen equipment) at an industrial scale is likely to be infeasible, considering the low volume availability of such residues worldwide or in any particular location; a very large (and expensive) number of broken panels or screens would be required to produce a useful quantity of concrete.…”
Section: Urban Wastesmentioning
confidence: 99%
“…Other types of waste glass, such as solar panel residue glass, have also been utilised in laboratory studies as a partial replacement material in metakaolin‐based activated cements. Although material performance seemed acceptable on a lab scale, the applicability of such processes (or those including post‐consumer glasses from electronic items such as display screen equipment) at an industrial scale is likely to be infeasible, considering the low volume availability of such residues worldwide or in any particular location; a very large (and expensive) number of broken panels or screens would be required to produce a useful quantity of concrete.…”
Section: Urban Wastesmentioning
confidence: 99%
“…In the analysis reported in this work, fine fractions were considered as low-grade glass, which could be used (according to current practice) directly in cement preparation or for the production of building materials (Hao et al, 2012;. Information about the tolerable amount of metals in waste glass from PVP in such material building formulation was not available.…”
Section: Experimental Results From Pilot and Lab Scalementioning
confidence: 99%
“…Surprisingly, even though glass is the main constituent of panels, it is not specifically addressed or characterized in the literature works regarding photovoltaic panels recycling. The final use of the recycling glass is not investigated at all: only some works (Hao et al, 2012; reported the addition of fine glass fractions (obtained by crushing and sorting of photovoltaic panels) in the formulation of building materials such as high density matrixes for civil engineering and glass-ceramics. This means recycling solar glass of panels as low-grade product against the priority of promoting high-quality recovery operations defined by the European Committee for Electrotechnical Standardization for photovoltaic panels (CENELEC EN50625-2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing reports in the literature only covered the use of recycled materials in sorted forms e.g. recycled concrete [10], bottom ash [11], waste glass [12] and wastepaper sludge [13] to be incorporated into geopolymers, and not as mixed forms that require minimal processing.…”
Section: Introductionmentioning
confidence: 99%